Diverse origins and pre-depositional histories of organic matter in contemporary Chinese marginal sea sediments. (15th October 2016) - Tao, Shuqin; Eglinton, Timothy I.; Montluçon, Daniel B.; McIntyre, Cameron; Zhao, Meixun
Abstract: Marginal seas are estimated to account for up to 90% of organic carbon (OC) burial in marine sediments, and thus play an important role in global carbon cycle. However, comprehensive assessments of carbon budgets for marginal sea systems are challenging due to their inherent complexity, with spatial and temporal variability in carbon inputs and dispersal processes. We examine the Bohai Sea and Yellow Sea (BS–YS) in order to further our understanding of sedimentary OC delivery, translocation and accumulation in a shallow marginal sea system. Bulk properties and the content and isotopic compositions (Δ 14 C, δ 13 C) of source-specific plant wax n -alkyl lipid biomarkers were determined for a suite of surficial sediment samples. Variable δ 13 C values (−25.1‰ to −28.5‰) and contemporary radiocarbon ages of short-chain n -fatty acids (FAs; C16, C18 ) reflect modern autochthonous marine and/or fresh terrestrial plant input. In contrast, extremely depleted Δ 14 C values (−932‰ to −979‰) of short-chain n -alkanes (C16, C18 ) suggest a predominant input from sedimentary rocks (petrogenic OC) or petroleum. Abundance-weighted average δ 13 C and Δ 14 C values of long-chain leaf wax lipids (C26+28+30 n -FAs, C24+26+28 n -alkanols, C27+29+31 n -alkanes) are −29.1 ± 1.1‰ to −30.2 ± 0.3‰, and −286 ± 150‰ to −442 ± 119‰, respectively, illustrating that terrestrial OC delivery is dominated by pre-aged (∼3000–5000  14 C yrs) C3 vegetation sources. A coupled carbon-isotopic mixing model, based on the bulk and compound-specific biomarker δ 13 C and Δ 14 C values, is used to partition the BS–YS sedimentary OC into three components that reflect both origins and transport processes. For all sampling sites, 31–64% is modern/contemporary OC, 24–49% is pre-aged terrestrial OC, and 7–26% is fossil OC, the latter likely derived from both physical erosion of ancient sedimentary rocks and fossil fuel sources. Pre-aged soil OC is most prominent in front of the modern and old Huanghe (Yellow River) delta (48% and 49%), and fossil OC is most significant north of the old Huanghe mouth (26%). Significant pre-aged soil contributions (33%) are also evident for sites further offshore, where transport and deposition of eolian dust supply may be important. For the three major deposition areas of the BS–YS system (Bohai Basin, sub-aqueous Huanghe delta and central south YS basin), we estimate that about 3.02 Mt/yr of refractory, plant-derived pre-aged soil OC and 0.98 Mt/yr of 14 C-depleted fossil OC accumulates in surface sediments, corresponding to 35% and 11% of sediment TOC, respectively. Compared with estimates for fluxes from corresponding sources, the burial efficiency is close to 100% for pre-aged soil OC and 70% for fossil OC, implying efficient OC burial in delta and shelf environments. Re-burial of these two pools of terrigenous OC only affects carbon cycling on millennial and longer timescales respectively, and exerts little influence on the modern carbon cycle (<100 yr). Carbon isotopic compositions of source specific biomarkers are a useful tool not only for constraining OC sources and transport vectors, but also for delineating their impact on the contemporary carbon cycling in marginal sea systems.